IMPLEMENTASI PROGRAM CORPORATE SOCIAL RESPONSIBILITY (CSR) PT SARI HUSADA MELALUI PEMBERDAYAAN PEREMPUAN â€œWARUNG ANAK SEHATâ€ DI SDN GONDOLAYU YOGYAKARTA - qonaah, siti qonaah (Universitas Bina Sarana Informatika, 2017)
Abstract - The Program Warung Anak Sehat (Was) initiated Â PT Sari husada is the implementation of a programme of corporat social responsibility have been implemented since the year 2011. The program has been embracing social responsibility corporat 100 school canteen vending in the city and County Daerah Istimewa Yogyakarta (DIY) called Ibu Warung Anak Sehat (IWAS). In building primary schools in different regions, the program WAS focused towards fulfillment of nutrition in accordance with the guidelines and the empowerment of women through micro. This research is to know the implementation of the program of corporate social responsibility (CSR) of PT Sari Husada Through women empowerment in Warung Anak Sehat SDN Gondolayu Yogyakarta. In this study the researchers used a qualitative approach and study cases, as a method of research that illustrates that through this activity is part of the corporate social responsibility activities in the field of community development through women's empowerment. Thus with corporate social responsibility through women's empowerment can improve nutrition of school children and capable of creating Advanced generation of Indonesia,Â Keywords- Corporate Social Responsibility, Women's Empowerment